(untitled) (Global Conference on Medical and Health Sciences, 2026)
Elderly patients with acute destructive cholecystitis and severe comorbidity often have limited hepatic reserves, and radical surgery in this group carries a high risk of postoperative liver failure, which aggravates the postoperative course and increases mortality. A dedicated method for preventing postoperative liver failure in high-risk patients has not been sufficiently developed.